PERAN ORANGTUA DALAM MEMPERKENALKAN BACAAN AL-QUR’AN PADA ANAK DI GAMPONG DALAM KECAMATAN SAMADUA KABUPATEN ACEH SELATAN - Muthmainnah; Heliati Fajriah; Anita Novira (FITRAH: International Islamic Education Journal, 2021)
Parents are educators who have a major role in the life of a child. The introduction of reading the Qur’an from an early age is one of the noble tasks carried out by parents as the first educator in the family. Based on initial observations in Gampong Dalam, South Aceh Regency. Researchers found that parents have a role in introducing the reading of the Qur'an to children. This is evidenced by the child's ability to recite the recitation of the Qur'an. Therefore, this study aims to determine the role of parents in introducing the reading of the Qur'an to Early Childhood in Gampong Dalam and the obstacles they face. This research is a descriptive qualitative research using interview sheets to collect data. The informants interviewed were 9 parents who have early childhood in the gampong. Based on the research data obtained, the researchers found that parents have a role in introducing the reading of the Qur'an to Early Childhood by means of; guiding, familiarizing, giving attention, recognizing difficulties, providing facilities, and using methods in introducing the reading of the Qur’an to children. The obstacles in introducing the reading of the Qur'an are found in parents and the environment.